Penyampaian pesan dakwah melalui musik aliran death metal oleh grup band “purgatory” - Hidayat, Sendy Nur (Maliki Interdisciplinary Journal, 2024)
Nowadays, da'wah does not only occur in recitation events at mosques or Muslim holiday celebrations, but can also be found in various forms of art, one of which is music. Music, as an art form, is an effective means of communication. Through lyrics or poetry in music, messages can be conveyed and influence listeners. Music is also part of mass communication through hearing. Music can be a means of conveying da'wah messages that are easily accepted by the public. One example of music that becomes a medium of propaganda is songs from the band Purgatory. Although carrying the flow of metal music, which is often considered by many people as music followed by followers of Satan, Purgatory is different from that opinion. Therefore, Purgatory is often referred to as a white metal band, which features songs with lyrics that convey a message of kindness. In this paper, researchers are interested in discussing the delivery of da'wah messages through death metal music by the band "Purgatory".